Convergence from the territorial approach: Case of the region of Piura - Peru, period 2007-2019 - Suarez Guerrero, Marvin (2021)
This research analyzes the effect of public investment on the convergence conditions in district development in the Piura Region (Peru) during the period 2007-2019. Convergence, as captured by the Human Development Index (HDI), is evaluated using two approaches: traditional beta convergence (absolute and conditional), and distributional analysis, to verify the dynamic behavior of the HDI over time (sigma convergence) and in space (spatial autocorrelation). The results allow us to verify that there is no convergence in Piura since the differences between the districts tend to increase over time (sigma divergence). Moreover, there is a polarization in the development within the region, due to the existence of a developed cluster and a lagging one. The research thus finds that public investment efforts are insufficient to reduce district inequalities. The challenges for convergence are structural in nature and include problems that strongly condition development in these areas, such as persistent poverty and the presence of spatial effects in the territory.